An examination of sugar-sweetened beverage tax regulations in six jurisdictions: Applying a social justice perspective to beverage taxation and exemptions - Natalie D. Riediger; Tamara Neufeld; Myra Tait; Lorna Turnbull; Kelsey Mann; Anne Waugh; Andrea Bombak (Taylor & Francis Group, 2024)
Taxes, legislation and politics are social determinants of health, which can impact health through multiple pathways. The purpose of this study was to review regulations regarding sugar-sweetened beverage (SSB) taxation and describe taxation/exemption of various beverage categories. We reviewed SSB taxation regulations from Mexico, the United Kingdom, Berkeley, Philadelphia, San Francisco and South Africa. Supplementary government documents and academic publications were also reviewed to further discern beverage taxation/exemption and zero-rating. There were a number of beverage types that fell clearly into typically taxed or exempt/zero-rated categories across all six jurisdictions (e.g. pop/soda as taxed and water as zero-rated). Exemptions and ambiguities within the six regulations can generally be grouped as a lack of clarity regarding the meaning and use of milk; the meaning of 'medical purposes' and 'supplemental'; the point at which a beverage is prepared; the form of concentrate (i.e. liquid/frozen/powder) or medium used (e.g. water, coffee); and location of preparation or business size of retailer. SSB tax regulations are complex, unclear, vary across jurisdiction and leave several beverage types with added sugar exempt from taxation or at risk of a legal challenge. Lastly, tax exemptions generally reflect and perpetuate existing sociopolitical dynamics within the food system.